Power-low expansion in k-essence cosmology - Chimento, Luis Pascual (2004)
We study spatially flat isotropic universes driven by k-essence. It is shown that Friedmann and k-field equations may be analytically integrated for arbitrary k-field potentials during evolution with a constant baryotropic index. It follows that there is an infinite number of dynamically different k-theories with equivalent kinematics of the gravitational field. We show that there is a large "window" of stable solutions, and that the dust-like behavior separates stable from unstable expansion. Restricting to the family of power law solutions, it is argued that the linear scalar field model, with constant function F, is isomorphic to a model with divergent speed of sound and this makes them less suitable for cosmological modeling than the nonlinear k-field solutions we find in this paper.